Dispersants, Conductive Agents and Lithium-ion Batteries

By using a dispersant containing comonomers, which is adsorbed on the surface of carbon nanotubes through π-π conjugation and utilizes steric hindrance and intermolecular repulsion, the difficulty in dispersing carbon nanotubes in lithium-ion batteries is solved. problem, achieving better dispersion and battery performance.

CN118580423BActive Publication Date: 2025-01-21ENVISION RUITAI DYNAMICS TECH (SHANGHAI) CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411055703.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-01-21
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

Carbon nanotubes are difficult to disperse in lithium-ion batteries, resulting in long dispersion time and poor slurry stability, which affects battery performance.

Method used

A dispersant including a first comonomer, a second comonomer and a third comonomer is used. The dispersant is adsorbed on the surface of the carbon nanotube through π-π conjugation, utilizing steric hindrance and intermolecular repulsion. Improve the dispersion effect of carbon nanotubes.

Benefits of technology

The dispersion effect of carbon nanotubes is improved, the dispersion time is shortened, the battery performance is improved, including improving the conductive performance and dynamic performance, while reducing the cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580423B_ABST
    Figure CN118580423B_ABST
Patent Text Reader

Abstract

Some embodiments of the present application provide a dispersant, a conductive agent and a lithium-ion battery, the dispersant comprising: a compound of general formula (I), (I) in general formula (I), R1 is selected from any one of the group consisting of,,, and; R2 is selected from any one of the group consisting of and, wherein R3 and R4 are each independently selected from an alkyl group having 1 to 3 carbon atoms; wherein a and b are in the range of 6 to 10, and a and b are the same or different, and x:y:z is 10 to 30:80 to 120:25 to 40.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and more particularly to dispersants and lithium-ion batteries. Background Art

[0002] With the development of new energy fields such as electric vehicles, the application of lithium-ion batteries has increased, and the performance requirements for them have become increasingly higher. Adding carbon nanotubes (CNTs) as conductive agents in lithium-ion batteries can improve their conductivity. They have a fibrous structure and can form a continuous conductive network in the electrode active material. At the same time, the pole piece with added carbon nanotubes has better toughness, which improves the problem of pole piece shedding during the cycle of lithium-ion batteries, thereby increasing the cycle life of lithium-ion batteries.

[0003] However, carbon nanotubes have a large specific surface area, and the p electrons of carbon atoms form a large range of delocalized π bonds. Due to the π-π interaction, carbon nanotubes tend to be closely aggregated with each other and are difficult to disperse. At present, the commonly used dispersion methods for carbon nanotubes mainly include grinding, stirring, ultrasonic dispersion, strong acid washing, adding surfactants, etc. In addition, when preparing carbon nanotube slurry, the traditional dispersant used is PVP (polyvinyl pyrrolidone), where the K value of PVP is between 25-30 for the best effect. However, using PVP as a dispersant to disperse carbon nanotubes alone not only takes a long time to disperse, but also has poor slurry stability and is easy to gel, resulting in difficulties in the use and transportation of carbon nanotube slurry, which in turn affects the performance of the prepared lithium-ion battery. Summary of the invention

[0004] The dispersant provided by the invention solves the problem that carbon nanotubes are difficult to disperse in lithium ion batteries, improves the dispersion effect of carbon nanotubes, and reduces process time.

[0005] Some embodiments of the present application provide a dispersant, including: a compound of general formula (I),

[0006] (I)

[0007] In the general formula (I), R1 is selected from , , , and Any one of the group consisting of; R2 is selected from and Any one of the group consisting of, wherein R3 and R4 are each independently selected from an alkyl group having 1 to 3 carbon atoms; wherein a and b are in the range of 6 to 10, and a and b are the same or different, and x:y:z is 10 to 30:80 to 120:25 to 40. For the above dispersant, as shown below, it has a first comonomer A, a second comonomer B and a third comonomer C.

[0008]

[0009] In the dispersant, the first comonomer plays a role in regulating the molecular weight, while ensuring that the anchoring groups are not too concentrated to cause the carbon nanotubes to agglomerate due to the redundant accumulation of the molecular structure. The second comonomer mainly plays a role in spatial repulsion, and the third comonomer plays a role in molecular repulsion. The three comonomers work synergistically to improve the efficient dispersion and stabilization of the dispersant.

[0010] In some embodiments, the molecular weight of the dispersant is between 20,000 and 30,000, because when the molecular weight of the dispersant is low (i.e., <20,000), the steric hindrance between the carbon nanotubes is limited, and there is a strong van der Waals attraction between the dispersed carbon nanotubes, so most of the carbon nanotubes still exist in the form of agglomerates and cannot play a good dispersion role. When the molecular weight of the dispersant is large (i.e., >30,000), it is also easy to play a bridging role between the carbon nanotubes and cause the carbon nanotubes to agglomerate and cannot be well dispersed.

[0011] In some embodiments, R1 is , or , and the R2 is or , wherein R3 and R4 are each independently selected from an alkyl group having 1 to 3 carbon atoms.

[0012] In some embodiments, a is 7 and b is 6.

[0013] In some embodiments, the dispersant is: , , , , or .

[0014] Other embodiments of the present application provide a conductive agent, including carbon nanotubes, the above-mentioned dispersant, an additional dispersant different from the dispersant, and a solvent, wherein based on the mass of the conductive agent, the mass percentages of the carbon nanotubes, the additional dispersant, the dispersant and the solvent are: 4~10%, 0.6~2%, 0.02~0.4%, 87.8~95.38%, respectively.

[0015] In some embodiments, the additional dispersant is polyvinylpyrrolidone.

[0016] In some embodiments, the molecular weight of the additional dispersant is in the range of 44,000-54,000. This is because when the molecular weight of the additional dispersant is in the range of 44,000-54,000, it will better affect the viscosity of the additional dispersant dispersion, so that the viscosity of the carbon nanotube slurry dispersed by the additional dispersant is smaller, the shear thinning behavior is relatively smooth, and the slurry stability is better.

[0017] In some embodiments, the dispersant is adsorbed on the surface of the carbon nanotubes via π-π conjugation.

[0018] Still other embodiments of the present application provide a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator, wherein the positive electrode sheet comprises the above-mentioned conductive agent.

[0019] Therefore, the present application solves the problem of difficult dispersion of carbon nanotubes by providing a dispersant, thereby improving the dispersion effect and improving battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Aspects of the present invention are best understood from the following detailed description when read with the accompanying figures.

[0021] Figure 1 The viscosity changes of the conductive agents of Example 1 and Comparative Example 1 of the present application are shown.

[0022] Figure 2 The relationship between the shear rate and viscosity of the conductive agent of Example 1 and Comparative Example 1 of the present application is shown.

[0023] Figure 3 The relationship between the shear rate and the shear stress of the conductive agent of Example 1 and Comparative Example 1 of the present application is shown.

[0024] Figure 4 The infrared spectra of the dispersants of Example 1 and Comparative Example 1 of the present application are shown.

[0025] Figure 5 The particle size distribution curves of the conductive agents of Example 1 and Comparative Example 1 of the present application are shown. DETAILED DESCRIPTION

[0026] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0027] The present application solves the problem of the difficulty in dispersing carbon nanotubes in lithium-ion batteries by providing a dispersant, thereby improving the performance of the corresponding lithium-ion batteries. Specifically, according to some embodiments, the present application provides a dispersant, which includes: a compound of general formula (I),

[0028] (I)

[0029] In the general formula (I), R1 is selected from , , , and Any one of the group consisting of; R2 is selected from and Any one of the group consisting of, wherein R3 and R4 are each independently selected from an alkyl group having 1 to 3 carbon atoms; wherein a and b can be selected from 6 to 10, and a and b are the same or different, and x:y:z is 10 to 30:80 to 120:25 to 40.

[0030] The above dispersant has a first comonomer A, a second comonomer B and a third comonomer C as shown below.

[0031]

[0032] In the dispersant, the first comonomer plays a role in regulating the molecular weight, while ensuring that the anchoring groups are not too concentrated to cause the carbon nanotubes to agglomerate due to the redundant accumulation of the molecular structure. The second comonomer mainly plays a spatial repulsion role, and the third comonomer plays an intermolecular repulsion role. The three comonomers work synergistically to improve the efficient dispersion and stabilization of the dispersant. Specifically, when a and b are in the range of 6 to 10, and a and b are the same or different, x:y:z is in the range of 10 to 30:80 to 120:25 to 40, and R1 and R2 are selected from the above functional group group, the dispersant has a good dispersion and stabilization effect.

[0033] In some specific embodiments, a can be selected as 5, and b can be selected as 4. If a and b are less than the range of 6-10, the above dispersant is insufficient to provide sufficient steric hindrance; if a and b are greater than this range, the synthesized molecular weight is large, dissolution is difficult, and it is easy to cause chain folding, resulting in a weakened dispersing effect of the above dispersant.

[0034] In addition, in the above dispersant, x:y:z is 10~30:80~120:25~40. If x:y:z is lower than 10:80:25, the above dispersant will not be able to provide enough anchoring sites, so that its steric hindrance is limited and insufficient to open the van der Waals attraction between carbon nanotubes, resulting in serious agglomeration of carbon nanotube slurry; at the same time, if x:y:z is higher than 30:120:40, it will affect the size of the molecular chain, making it easy to play a bridging role between carbon nanotubes and cause carbon nanotubes to agglomerate.

[0035] The dispersant provided in the present application can be adsorbed on the surface of carbon nanotubes through π-π conjugation by using pyrrolidone, pyrrole, benzene ring, pyridine, imidazole, etc. as anchoring groups, and stably disperse the carbon nanotubes through steric hindrance as a stabilizing mechanism.

[0036] In some embodiments, the molecular weight of the dispersant is between 20,000 and 30,000. When the molecular weight of the dispersant is low (i.e., <20,000), the steric hindrance between the carbon nanotubes is limited, and there is a strong van der Waals attraction between the dispersed carbon nanotubes. Therefore, most of the carbon nanotubes still exist in the form of aggregates and cannot play a good dispersion role. When the molecular weight of the dispersant is large (i.e., >30,000), it is also easy to play a bridging role between the carbon nanotubes and cause the carbon nanotubes to agglomerate and cannot be well dispersed.

[0037] Furthermore, in the above dispersant, R1 can be selected from , or , R2 can be selected as or , R3, R4 are each independently selected from an alkyl group having 1 to 3 carbon atoms. , The π bond range is larger, and the π-π structure can be generated with carbon nanotubes, which has a better dispersion effect on carbon nanotubes; for R2, The structure can generate electrostatic repulsion between molecules to form a double electric layer, which complements the stability of the slurry and makes the dispersant more stable.

[0038] In some specific embodiments, the dispersant may be: , , , , or .

[0039] Other embodiments of the present application provide a conductive agent, including carbon nanotubes, the above-mentioned dispersant, an additional dispersant different from the dispersant, and a solvent, wherein, based on the mass of the conductive agent, the mass percentages of the carbon nanotubes, the additional dispersant, the dispersant, and the solvent are: 4~10%, 0.6~2%, 0.02~0.4%, and 87.8~95.38%, respectively. Optionally, the mass ratio of the additional dispersant to the dispersant can be in the range of 4:1~40:1. In some specific embodiments, the additional dispersant is polyvinyl pyrrolidone. Further, the K value of the additional dispersant is in the range of 25~30, because the viscosity of the carbon nanotube slurry dispersed by the additional dispersant with a K value between 25~30 is small, the shear thinning behavior is relatively gentle, and the slurry stability is good. Further, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0040] In the above embodiment, the dispersant is adsorbed on the surface of the carbon nanotubes through π-π conjugation. Specifically, the dispersant is adsorbed on the surface of the carbon nanotubes through π-π conjugation using pyrrolidone, pyrrole, benzene ring, pyridine, imidazole, etc. as anchoring groups, and the carbon nanotubes are stably dispersed through steric hindrance as a stabilization mechanism.

[0041] The conductive agent of the present application can be used in the formulation system of lithium-ion batteries to improve the stability of the positive electrode slurry, so that the conductive agent such as carbon nanotubes is evenly dispersed, the conductivity is improved, and the dynamic performance is better; at the same time, the dispersion time of carbon nanotubes can be shortened and the cost can be reduced. In addition, the amount of dispersant added should be selected within a suitable range, such as based on the mass of the conductive agent, the mass percentages of carbon nanotubes, additional dispersants, dispersants and solvents are in the range of 4-10%, 0.6-2%, 0.02-0.4%, and 87.8-95.38%, respectively, because too little dispersant is not enough to provide sufficient dispersibility, resulting in poor stability of the corresponding slurry; conversely, too much dispersant will lead to increased impedance and increased costs.

[0042] Still other embodiments of the present application provide a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator, wherein the positive electrode sheet comprises the above-mentioned conductive agent.

[0043] The synthesis method of the dispersant is as follows:

[0044] Ethylene, , , add it to the solvent, react for 5 to 8 hours under the action of initiator and catalyst in N2 atmosphere, and the reaction temperature is 80 to 180°C to obtain the above-mentioned dispersant.

[0045] In the above method, the solvent may include but is not limited to one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), water, hexane, and N-methylpyrrolidone. The amount of the solvent is 2 to 5 times the total amount of the reactants by weight. The total amount of the reactants is ethylene, , total mass.

[0046] The initiator includes, but is not limited to, one or more of azobisisobutyronitrile, cumene hydroperoxide, tert-butyl perbenzoate, benzoyl peroxide / ferrous pyrophosphate, and the amount of the initiator used is 1-2% of the total amount of the reactants by mass.

[0047] The catalyst includes but is not limited to one or more of triethylamine, chromium oxide, and molybdenum oxide. The amount of the catalyst used is 1-2% of the total amount of the reactants by weight.

[0048] The synthesis method of the conductive agent (ie, carbon nanotube slurry) is as follows:

[0049] 1) The amount and ratio of each component

[0050] The mass percentages of carbon nanotubes: additional dispersant: dispersant: NMP (N-methylpyrrolidone) are (4-10%), (0.6-2%), (0.02-0.4%), and (87.8-95.38%) respectively;

[0051] The mass ratio of additional dispersant: dispersant can be (4:1)~(40:1);

[0052] The carbon nanotubes may include single-walled carbon nanotubes and / or multi-walled carbon nanotubes;

[0053] Carbon nanotubes need to meet the following requirements: BET (carbon nanotube specific surface area) > 200 m 2 / g, carbon nanotube length (5~50μm), tube diameter (2~25nm), purity>97%, water content<1000ppm;

[0054] The additional dispersant is PVP (polyvinyl pyrrolidone), with a K value between 25 and 30 and a molecular weight between 24,000 and 54,000.

[0055] 2) Preparation of Conductive Agent (i.e., Carbon Nanotube Slurry)

[0056] The additional dispersant and the above dispersant are dispersed in advance, that is, the additional dispersant and the dispersant are dissolved in the solvent, and then the carbon nanotubes are pre-dispersed, that is, the carbon nanotubes are added to the above solvent, and then sand-milled to obtain the conductive agent (that is, carbon nanotube slurry). The details are as follows:

[0057] ① Additional dispersant and dispersant dispersion: Add additional dispersant PVP and the above dispersant provided in the present application to NMP and disperse for 15 to 30 minutes to obtain a dispersant solution.

[0058] ② Pre-dispersion of carbon nanotubes: Add 1 / 2 carbon nanotube powder to the above dispersant solution and disperse it by stirring and circulating for 10 to 30 minutes;

[0059] Afterwards, the remaining 1 / 2 carbon nanotube powder is added to the above solution and the dispersion is continued in a circulating manner for 10 to 30 minutes to obtain a slurry containing carbon nanotubes.

[0060] ③ Sand milling: The above slurry containing carbon nanotubes is sand milled for 2 to 12 hours to obtain a conductive agent (ie, carbon nanotube slurry).

[0061] The sand mill can be selected from horizontal, vertical, disc and pin sand mills.

[0062] The filling amount of zirconium beads is 70~85% (mass percentage), and the size of zirconium beads is 0.7~1.2mm;

[0063] Sand mill speed 1500~2400rpm / min;

[0064] The temperature is less than 60° C., the slurry viscosity is less than 3000 mPa∙S, and the solid content of the slurry containing carbon nanotubes is 4-20% (mass percentage).

[0065] Among the above-mentioned conductive agents, the sand mill speed, sand milling time, use of zirconium beads, etc. will also affect the stability of the carbon nanotube slurry (conductive agent). If they exceed the above range, the stability of the carbon nanotube slurry will deteriorate.

[0066] Positive electrode

[0067] The positive electrode sheet in the lithium-ion battery provided in the present application includes a positive electrode current collector commonly used in the art and a positive electrode slurry containing the above-mentioned conductive agent disposed on the positive electrode current collector. The current collector can be, for example, aluminum foil and nickel foil, and the positive electrode slurry is as follows:

[0068] In terms of mass percentage, the amount of positive electrode active material added is (91.5~98.8wt%), conductive agent (0.2~1.5wt%), additional conductive agent (0.5~4%), and binder (0.5~3%).

[0069] The positive electrode active material may include but is not limited to LiCoO2 with a hexagonal layered crystal structure; LiMn2O4 with a cubic spinel crystal structure; LiFePO4 with an orthorhombic olivine crystal structure; layered structure positive electrode materials: such as ternary materials NCM and NCA, NCM ternary materials may include NCM111 (indicating that the ratio of Ni:Co:Mn in nickel, cobalt and manganese is 1:1:1), NCM523 (indicating that the ratio of Ni:Co:Mn in nickel, cobalt and manganese is 5:2:3), NCM622 (indicating that the ratio of Ni:Co:Mn in nickel, cobalt and manganese is 6:2:2), NCM811 (indicating that the ratio of Ni:Co:Mn in nickel, cobalt and manganese is 8:1:1), etc.; lithium-rich materials; polyanion positive electrode materials: such as lithium manganese phosphate and lithium cobalt phosphate; polyanion positive electrode materials, such as silicates, borates, sulfates, etc.

[0070] The conductive agent is the conductive agent prepared as described above (ie, carbon nanotube slurry).

[0071] The additional conductive agent is one or more of SP (conductive carbon black), conductive graphite KS-6, acetylene black, carbon fiber, Ketjen black, and graphene.

[0072] The binder may include, but is not limited to, one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and ethylene-tetrafluoroethylene copolymer.

[0073] Negative electrode

[0074] The negative electrode plate includes negative electrode active materials, including artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based, tin-based negative electrode materials, lithium titanate negative electrode materials, etc. The negative electrode plate also includes a thickener CMC (sodium carboxymethyl cellulose) and a binder SBR (lithium styrene-butadiene latex). The solvent of the negative electrode plate is a good solvent for the binder, such as polar solvents acetonitrile, water, N-methylpyrrolidone, etc., and the solid content is 55%.

[0075] The negative electrode current collector includes a copper current collector, and the negative electrode material, in some embodiments, the conductive agent includes conductive carbon black (SP).

[0076] Electrolyte

[0077] The above-mentioned lithium-ion battery also includes an electrolyte, which is a non-aqueous electrolyte and includes but is not limited to a commercial electrolyte. Specifically, the electrolyte includes a lithium salt, a non-aqueous solvent and an additive. The non-aqueous solvent can be a conventional non-aqueous solvent in the art, including one or more of carbonate esters, ester solvents of carboxylic acid esters, and ether solvents, preferably an ester solvent, and more preferably a carbonate solvent. Among them, the carbonate solvent is preferably one or more of ethylene carbonate, diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).

[0078] The lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or lithium bis(oxalatoborate) (LiBOB), and preferably has a content of 5% to 20% in the electrolyte.

[0079] The additives mainly include negative electrode film-forming additives, which can be one or more of 1,3-propane sultone (PS), vinylene carbonate (VC), fluoroethylene carbonate (FEC), diethylene sulfate (DTD) or lithium difluorophosphate (LiPO2F2). The conventional amount of additives in the electrolyte is 1% to 4% of the electrolyte, for example, 2%.

[0080] Isolation film

[0081] In some embodiments, the lithium-ion battery further includes a separator, which is located between the positive electrode sheet and the negative electrode sheet. For example, the separator includes a separator of a substrate layer and a surface treatment layer; the substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, polypropylene porous membrane, polyethylene porous membrane, polypropylene non-woven fabric, polyethylene non-woven fabric, polypropylene-polyethylene-polypropylene porous composite membrane can be selected. A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance.

[0082] Lithium-ion battery

[0083] The positive electrode sheet, negative electrode sheet, electrolyte and separator described above can be assembled into a lithium-ion battery by the methods commonly used in the art, wherein the positive electrode sheet, separator, negative electrode sheet, etc. are wound or stacked in sequence into a bare battery cell, and then encapsulated in, for example, an aluminum-plastic film, and an electrolyte is injected. After formation, packaging and testing, the assembled lithium-ion battery is subjected to electrochemical performance tests and cycle performance tests.

[0084] Those skilled in the art will understand that the above-described method for preparing a lithium-ion battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.

[0085] The reagents and raw materials used in the present invention are commercially available.

[0086] The present invention has no special requirements on the assembly method of the above-mentioned all-solid-state lithium-ion battery, and an assembly method familiar to those skilled in the art can be used.

[0087] Some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0088] Example 1

[0089] (1) Preparation of conductive agent (carbon nanotube slurry)

[0090] ① Preparation of dispersant:

[0091] 20 mol of ethylene, 100 mol 、30mol Add to N,N-dimethylformamide, react for 6 hours under the action of initiator and catalyst in N2 atmosphere, the reaction temperature is 135°C, wherein the initiator is azobisisobutyronitrile, and the amount of the initiator is 1.5% of the total amount of the reactants by weight, and the catalyst is triethylamine, and the amount of the catalyst is 1.5% of the total amount of the reactants by weight, thereby obtaining a dispersant, which is shown as follows:

[0092] .

[0093] Note that in the above embodiment, x:y:z is 20:100:30, a is 7 and b is 6.

[0094] ② Disperse the additional dispersant polyvinyl pyrrolidone (molecular weight between 44000-54000) and the above dispersant in NMP for 30 minutes to obtain a dispersant solution, add 1 / 2 of the carbon nanotube powder to the above solution and disperse for 15 minutes, then add the remaining 1 / 2 of the carbon nanotube powder and disperse for 15 minutes, and sand grind for 5 hours to obtain the conductive agent of the carbon nanotube slurry. In this method, the sand grinder speed is 2100rpm, the zirconium bead filling amount is 80%, and the zirconium bead size is 0.8mm.

[0095] The mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP are 5%, 0.83%, 0.17%, and 94%, respectively.

[0096] (2) Preparation of positive electrode

[0097] The positive electrode active material NCM622, conductive agent, SP, and binder PVDF (polyvinylidene fluoride) are evenly dispersed in a solvent according to the mass percentage of 97.2%, 0.8%, 1.0%, and 1.0%, respectively. The solvent is NMP with a solid content of 75%. They are coated on the positive electrode collector and then dried, rolled, and cut to form a positive electrode sheet.

[0098] In some embodiments, the positive electrode current collector can be an aluminum foil of 5~20μm, or a composite current collector of 10~15μm (the composite current collector uses a polymer insulating resin material as a "sandwich" layer, with aluminum deposited on the upper and lower surfaces. The polymer resin can be polyethylene terephthalate PET, polypropylene PP, polyimide PI, polystyrene PS, or polyamide PA).

[0099] (3) Preparation of negative electrode sheet

[0100] The negative electrode active materials artificial graphite, SP, thickener CMC, and binder SBR are evenly dispersed in a solvent according to mass percentages of 96.6%, 0.4%, 2%, and 1.0%, respectively, wherein the solvent is water with a solid content of 55%, and are coated on the negative electrode collector and then dried, rolled, and cut to form a negative electrode sheet.

[0101] The negative electrode current collector can be a copper foil of 5~15μm, or a composite current collector of 10~15μm (the composite current collector uses a polymer insulating resin material as a "sandwich" layer, with copper deposited on the upper and lower surfaces. The polymer resin can be polyethylene terephthalate PET, polypropylene PP, polyimide PI, polystyrene PS, or polyamide PA).

[0102] (4) Preparation of isolation membrane

[0103] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0104] (5) Preparation of electrolyte

[0105] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92 is used as the electrolyte of the lithium-ion battery.

[0106] (6) Preparation of lithium-ion batteries

[0107] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation. After roller pressing and die cutting, the lithium-ion battery is prepared through winding, packaging, liquid injection, and other processes.

[0108] Example 2

[0109] The preparation method is consistent with that of Example 1, except that the dispersant in Example 2 is as follows:

[0110] .

[0111] Example 3

[0112] The preparation method is consistent with that of Example 1, except that the dispersant in Example 3 is as follows:

[0113] .

[0114] Example 4

[0115] The preparation method is consistent with that of Example 1, except that the dispersant in Example 4 is as follows:

[0116] .

[0117] Example 5

[0118] The preparation method is consistent with that of Example 1, except that the dispersant in Example 5 is as follows:

[0119] .

[0120] Example 6

[0121] The preparation method is consistent with that of Example 1, except that the dispersant in Example 6 is as follows:

[0122] .

[0123] Example 7

[0124] The preparation method is consistent with that of Example 1, except that the dispersant in Example 7 is as follows:

[0125] .

[0126] Example 8

[0127] The preparation method is consistent with that of Example 1, except that the dispersant in Example 8 is as follows:

[0128] .

[0129] Example 9

[0130] The preparation method is consistent with that of Example 1, except that the dispersant in Example 9 is as follows:

[0131] .

[0132] Example 10

[0133] The preparation method is consistent with that of Example 1, except that the dispersant in Example 10 is as follows:

[0134] .

[0135] Embodiment 11

[0136] The preparation method is consistent with that of Example 1, except that the dispersant in Example 10 is as follows:

[0137] .

[0138] Example 12

[0139] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 4 are 5%, 0.937%, 0.063%, and 94%, respectively.

[0140] Embodiment 13

[0141] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 5 are 5%, 0.976%, 0.024%, and 94%, respectively.

[0142] Embodiment 14

[0143] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 6 are 5%, 1.406%, 0.094%, and 93.5%, respectively.

[0144] Embodiment 15

[0145] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 7 are 5%, 1.923%, 0.077%, and 93%, respectively.

[0146] Example 16

[0147] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 8 are 4%, 0.6%, 0.02%, and 95.38%, respectively.

[0148] Embodiment 17

[0149] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 9 are 10%, 2%, 0.2%, and 87.8%, respectively.

[0150] Embodiment 18

[0151] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 10 are 10%, 1.8%, 0.4%, and 87.8%, respectively.

[0152] Embodiment 19

[0153] The preparation method is consistent with that of Example 1, except that the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone, dispersant, and NMP in the conductive agent in Example 11 are 8%, 1.6%, 0.2%, and 90.2%, respectively.

[0154] Comparative Example 1

[0155] The preparation method is consistent with that of Example 1, except that the dispersant in Comparative Example 1 is as follows:

[0156] .

[0157] Comparative Example 2

[0158] The preparation method is consistent with that of Example 1, except that the dispersant in Comparative Example 2 is as follows:

[0159] .

[0160] Comparative Example 3

[0161] The preparation method is consistent with that of Example 1, except that the dispersant in Comparative Example 3 is as follows:

[0162] .

[0163] Comparative Example 4

[0164] The preparation method is consistent with that of Example 1, except that the dispersant in Comparative Example 4 is as follows:

[0165] .

[0166] Comparative Example 5

[0167] The preparation method is consistent with that of Example 1, except that the conductive agent in Example 5 is made of carbon nanotubes, additional dispersant polyvinyl pyrrolidone and NMP, and the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone and NMP are 5%, 1.0% and 94% respectively, and the sanding time is 16 hours.

[0168] Comparative Example 6

[0169] The preparation method is consistent with that of Example 1, except that the conductive agent in Example 6 is made of carbon nanotubes, additional dispersant polyvinyl pyrrolidone and NMP, and the mass percentages of carbon nanotubes, additional dispersant polyvinyl pyrrolidone and NMP are 5%, 2.0% and 93% respectively, and the sanding time is 16 hours.

[0170] Next, the testing method of lithium-ion batteries is described.

[0171] 1) Viscosity test:

[0172] The test was conducted using Brookfield Rotational Viscometer, using 61# and 62# testers, with a rotation speed of 12rpm / min.

[0173] Rotate the lifting knob to slowly lower the instrument and gradually immerse the rotor in the liquid to be measured until the rotor liquid level mark is level with the liquid level, then start measuring.

[0174] 2) Conductive agent (carbon nanotube slurry) stability test:

[0175] The positive electrode slurry was left to stand for 0, 1h, 2h, 2D, 7D, 14D, and 30D, and its viscosity change was tested. Figure 1 shown.

[0176] 3) Rheological test:

[0177] Anton Paar rheometer was used, the test temperature was 25±0.5℃, and the shear rate was increased from 0 to 600 1 / s;

[0178] Install the rotor, adjust the zero automatically, add the material, select the steady-state shear test module, and start testing the relationship between shear rate, viscosity and shear stress. Figure 2 and Figure 3 shown.

[0179] 4) Infrared test:

[0180] Tianjin Gangdong FTIR-7600 Fourier transform infrared spectrometer was used to put the prepared dispersant sample into the sample cell and start the test to obtain the frequency domain spectrum with wavelength or wave number as a function, such as Figure 4 shown.

[0181] 5) Particle size test:

[0182] Use Malvern Panalytical laser particle size analyzer, click the cleaning button on the sampler control software interface to clean the sampler and the conductive agent sample pool prepared above, and clean it 3-5 times. Pour the conductive agent sample prepared above into the sample slot of the sampler, with the stirrer speed of 700 rpm, the pump speed of 1750 rpm, and the ultrasonic power of 40W. When the shading degree is within the appropriate range, start the measurement and obtain the particle size distribution curve, as shown in Figure 5 shown.

[0183] 6) Diaphragm resistivity test:

[0184] The resistivity of the film was tested using Hioki RM2610, and a 3×3 cm electrode was cut. The positive electrode was placed in the test fixture and the resistivity of the dressing layer was obtained by measuring.

[0185] 7) Ratio test:

[0186] The prepared lithium ion battery was charged to 4.2V with 1 / 3C constant current, charged to 0.05C with constant voltage, left for 30 min, discharged to 3V with 1 / 3C0, left for 30 min, and the discharge capacity C0 was recorded; the battery was charged to 4.2V with 1 / 3C0 with constant current, charged to 0.05C0 with constant voltage, left for 30 min, discharged to 3V with 1 / 3C0, left for 30 min, and the discharge capacity C1 was recorded; the battery was charged to 4.2V with 1 / 3C0 with constant current, charged to 0.05C0 with constant voltage, left for 30 min, discharged to 3V with 3C, left for 30 min, and the discharge capacity Cn was recorded; the 3C capacity retention rate was Cn / C1×100%.

[0187] 8) DCR (Data Transfer Rate) Test:

[0188] Charge the cell with 1 / 3C constant current to 4.2V, charge it with constant voltage to 0.05C, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C0, charge it with 1 / 3C0 constant current to 4.2V, charge it with constant voltage to 0.05C0, let it sit for 30min, discharge it with 1 / 3C0 for 180min, let it sit for 10min, record the end voltage V0, discharge it with 2C for 30s, record the end voltage V1, discharge DCR=(V0-V1) / I.

[0189] 9) Cycle performance test:

[0190] Charge the cell with 1 / 3C constant current to 4.2V, charge it with constant voltage to 0.05C, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C0, charge it with 1 / 3C0 constant current to 4.2V, charge it with constant voltage to 0.05C0, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C1', and record the discharge capacity Cn' at the end of each cycle in this way. The cycle capacity retention rate is Cn' / C1' ×100%, and the number of cycles N when the retention rate is 80% is recorded.

[0191] Table 1 shows the experimental results of Examples 1-19 and Comparative Examples 1-6.

[0192] Table 1

[0193]

[0194]

[0195]

[0196] Depend on Figure 1 And by comparing Examples 1 to 19 with Comparative Examples 1-6, it can be seen that the conductive agent (carbon nanotube slurry) prepared by the present method has good stability, the initial viscosity is in the range of 100.30 mPa·S to 1430 mPa·S, and the viscosity after standing for 30 days can reach 420 mPa·S. In addition, it can be seen from Table 1 above that the membrane resistivity of the lithium ion battery prepared in Examples 1 to 19 is significantly reduced, and the 3C capacity retention rate, DCR performance and cycle performance are significantly enhanced, and the cycle performance can be between 1303 (see Example 16) and 1567 (see Example 18). This is because the use of the dispersant of the present application improves the dispersion effect of the carbon nanotubes, and the conductive agent of the prepared carbon nanotube slurry can improve the stability of the positive electrode slurry, so that the conductive agent such as carbon nanotubes is evenly dispersed, the conductive performance is improved, and the kinetic performance is better, thereby improving the 3C capacity retention rate, DCR performance and cycle performance of the corresponding lithium ion battery; at the same time, the dispersion time of the carbon nanotubes can be shortened, thereby reducing the cost.

[0197] Specifically, referring to Examples 1-11, for the dispersant provided in the present application, R1 is selected from , , , and The group consisting of: R2 is selected from and The present invention relates to a group of carbon nanotubes, wherein R3 and R4 are each independently selected from an alkyl group having 1 to 3 carbon atoms, and when a and b are in the range of 6 to 10, and a and b are the same or different, and x:y:z is in the range of 10 to 30:80 to 120:25 to 40, the dispersant has good dispersing and stabilizing effects and can improve the dispersion effect of carbon nanotubes.

[0198] Furthermore, it can be seen from Examples 12-19 that the conductive agent formed by the dispersant is made of carbon nanotubes, an additional dispersant polyvinyl pyrrolidone, a dispersant and NMP, and when the mass ratio and mass percentage of the carbon nanotubes, the additional dispersant polyvinyl pyrrolidone, the dispersant and the NMP in the conductive agent are in the range of 4-10%, 0.6-2%, 0.02-0.4% and 87.8-95.38%, respectively, the conductive agent such as carbon nanotubes can be evenly dispersed, the conductive performance is improved, and the dynamic performance is better.

[0199] In addition, from the comparison between Example 1 and Comparative Examples 1-2, it can be seen that if x:y:z is lower than 10:80:25, the above-mentioned dispersant will not be able to provide sufficient anchoring sites, so that its steric hindrance is limited and insufficient to open the van der Waals attraction between the carbon nanotubes, resulting in serious agglomeration of the carbon nanotube slurry; at the same time, if x:y:z is higher than 30:120:40, it will affect the size of the molecular chain, making it easy to play a bridging role between the carbon nanotubes and cause the carbon nanotubes to agglomerate.

[0200] From the comparison between Example 1 and Comparative Examples 3-4, it can be seen that if a and b are less than the range of 6-10, the above dispersant is insufficient to provide sufficient steric hindrance; if a and b are greater than this range, the synthesized molecular weight is large, dissolution is difficult, and it is easy to cause chain folding, resulting in a weakened dispersing effect of the above dispersant. Figure 2 The relationship between shear rate and viscosity shown in the figure shows that the conductive agent (carbon nanotube slurry) prepared in Example 1 has a relatively small dispersion viscosity, a relatively gentle shear thinning behavior, and a strong steric hindrance between particles, which can effectively prevent the aggregation of particles and is similar to a Newtonian fluid. Figure 3 From the relationship between shear rate and stress shown, it can be seen that the conductive agent (carbon nanotube slurry) polymer prepared in Example 1 can generate a strong steric repulsion force to offset the van der Waals force between particles. The slurry has a lower viscosity and can flow under a lower shear stress, resulting in a better dispersion effect.

[0201] Figure 4 Infrared spectrum of the dispersant prepared in Example 1, 1660-1680cm -1 -C=O stretching vibration; 1420cm -1 -CH2- bending vibration, 1300cm -1-CN- stretching vibration; 3100-3500cm -1 -NH- stretching vibration, 1049cm -1 It is a -CN- vibration peak, which indicates the presence of pyrrolidone and amino structures in the molecule.

[0202] Figure 5 It can be seen that the conductive carbon nanotube slurry prepared in Example 1 has a smaller particle size and a more concentrated particle size distribution.

[0203] Those skilled in the art should understand that the above embodiments are merely exemplary embodiments and that various changes, substitutions and alterations may be made without departing from the spirit and scope of the present application.

Claims

1. A dispersant, characterized in that: include: The compound of general formula (I), (I) In the general formula (I), R1 is selected from , , , and Any one of the groups consisting of; R2 is selected from and Any one of the group consisting of, wherein R3 and R4 are each independently selected from an alkyl group having 1 to 3 carbon atoms; Among them, a and b range from 6 to 10, and a and b are the same or different, and x:y:z is 10~30:80~120:25~40.

2. The dispersant according to claim 1, characterized in that The molecular weight of the dispersant is between 20,000 and 30,000.

3. The dispersant according to claim 1, characterized in that a is 7, and b is 6.

4. The dispersant according to claim 1, characterized in that The dispersant is: , , , , or .

5. A conductive agent, characterized in that: It comprises carbon nanotubes, a dispersant according to any one of claims 1 to 4, an additional dispersant different from the dispersant, and a solvent, wherein based on the mass of the conductive agent, the mass percentages of the carbon nanotubes, the additional dispersant, the dispersant and the solvent are 4-10%, 0.6-2%, 0.02-0.4% and 87.8-95.38%, respectively.

6. The conductive agent according to claim 5, characterized in that: The additional dispersant is polyvinyl pyrrolidone.

7. The conductive agent according to claim 5, characterized in that The molecular weight of the additional dispersant is in the range of 44,000-54,000.

8. The conductive agent according to claim 5, characterized in that The dispersant is adsorbed on the surface of the carbon nanotubes through π-π conjugation.

9. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet comprises the conductive agent according to claim 5.

Citation Information

Patent Citations

  • Ethylene / alpha-olefin / functionalized styrene derivative terpolymer and preparation method thereof

    CN113968926A

  • Dispersing agent, positive electrode material containing dispersing agent and lithium ion battery

    CN116314819A